North East Frontier Agency (Revised Draft) Fourth Five Year Plan - Planning Commission (Planning Commission, 1966)
During the last three Five Year Plans, the basic aims and objectives of the NEFA development plans were to improve the economic condition of the tribal people, without in any way interfering with their normal way of life, by providing them with the minimum essential social services, opening up the area for easy communication and generally to raise the standard of living of the people by introducing measures to enable them to earn supplementary income.
Planning and Development Department, North East Frontier Agency